2022
DOI: 10.1111/hdi.13016
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification is a risk factor for intradialytic hypotension in patients undergoing hemodialysis

Abstract: Introduction:We investigated the association between intradialytic hypotension (IDH) and coronary artery calcification and their effects on mortality in hemodialysis (HD) patients.Methods: Consecutive patients undergoing maintenance HD were enrolled. The study timeline included the baseline (day 1), exposure assessment (day 1-day 22), and outcome assessment (day 23-3 years) periods. IDH was defined as a nadir systolic blood pressure (SBP) of <100 mmHg or vasopressor use during at least 2 of 10 HD sessions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Mizuiri et al . [ 56 ] demonstrated that IDH is more frequently associated with CAC and patients with both IDH and CAC have a 3-year reduction in cumulative survival, a greater risk of CV events at 3 years, and a higher hazard ratio for CV mortality.…”
Section: Ckd and Cad: Epidemiology And Pathophysiologymentioning
confidence: 99%
“…Moreover, Mizuiri et al . [ 56 ] demonstrated that IDH is more frequently associated with CAC and patients with both IDH and CAC have a 3-year reduction in cumulative survival, a greater risk of CV events at 3 years, and a higher hazard ratio for CV mortality.…”
Section: Ckd and Cad: Epidemiology And Pathophysiologymentioning
confidence: 99%
“…Some studies have found potential predictors of IDH, such as TNF-α, IL-1 β [17] , propeptide level (Δ Prot) [18], Δ OER (oxygen uptake rate) [19], coronary artery calcium score (CACS) [20] and so on. Studies have shown that Δ OER > 19% 15 minutes after the start of dialysis or > 36% final increment at the end of dialysis can help identify high-risk IDH patients with hemodynamic instability, but this method can only be applied to patients with permanent central venous catheters [19].…”
Section: Biomarkers and Potential Predictorsmentioning
confidence: 99%